Real-time event area localisation and estimation in smart environments based on a realistic sensing model. (23rd November 2021) - Kundu, Srabani; Das, Nabanita; Saha, Dibakar
The need for early warning systems to design a smart environment is growing rapidly. A lot of works has been reported so far for generating an early warning in case of any disaster like gas leakage, forest fire, etc. using WSNs. In most of the works, it has been assumed that a node is affected whenever it lies within the event region. But in reality, each node does not sense just its point of location but covers a region defined by its sensing range and extracts an aggregated view of the region. So far, no sensing model considers this fact. In this paper, a new realistic sensing model is proposed for continuous event regions. Based on that, a lightweight localised algorithm is developed to identify a minimal set of boundary nodes to locate and estimate the event area in real-time achieving 99% accuracy and 75-80% reduction in message overhead.